Kereta Sewa Jimat: Car Rental System with Fuel Update - Muhamad Shukri, Muhammad Aliff; Bin Sahid, Mohd Zanes (Applied Information Technology And Computer Science, 2024)
Car rental services provide a solution for everyone to temporarily use a car for diverse purposes. However, it includes problems that might occur like human error during booking process, incomplete rental car information, and oversight in refuel when using the rental car. Objectives of this system are to design the car rental system using an object-oriented approach, develop it as a mobile application, and test it using User Acceptance Testing. Furthermore, the scope includes several modules, like the booking module, the rental car catalog module, and fuel update module. This system adheres to the prototyping model methodology, and some procedures have been followed to develop the system, which are communication, quick planning, modelling, prototyping, and deployment with feedback. The testing and feedback collection have been completed to understand user experiences with the system. This can streamline the car rental booking process for customers and impoves efficiency in management for staff.